KONSTRUKSI MEDIA TERHADAP THE JAKMANIA OLEH MEDIA CETAK KOMPAS SELAMA PUTARAN I DAN II LIGA SUPER INDONESIA 2009/2010 (ANALISA KAJIAN CULTURAL CRIMINOLOGY) - Sasyabella Febriani (Jurnal Kriminologi Indonesia, 2011)
This study attempts to explain the media construction of the Jakmania constructed by Kompas newspaper during the Round I and II Super League Indonesia (LSI) 2009/2010. Data was obtained through content analysis, observation and interviews. Both sources of data were combined and analyzed to see how the construction of reality of the Jakmania. This study is an analysis of cultural criminology studies, so media construction is analyzed in depth as a tool to show war between dominant culture and weak culture. The results of this study indicate that the newspaper headline as a print media, capable of constructing supporters group by distorting the image according to the stereotype of a stronger culture.